Language policies and sociolinguistic domains in the context of minority groups in China. Issue 2 (7th February 2018) - Feng, Anwei; Adamson, Bob
ABSTRACT: In mainland China, most ethnic minority students today face the challenge of learning three languages in schools, namely, their home language (L1), Mandarin Chinese (L2) and a foreign language, usually English (L3). Research into trilingual education for minority groups has been most active since the turn of the twenty-first century. This paper offers an overview of recent research, depicting major models adopted by minority schools and the contextual factors leading to the models in various minority regions in China. The paper begins with an account of state policies relevant to language provision for minority groups in China, which is followed by a discussion of the outcomes and models of trilingual education. A critical analysis is then made of contextual factors such as ethnolinguistic vitality, history, economy, geopolitics and the changing status of the three languages that affect trilingual education for minority groups. The paper argues that language policymaking in different domains including families, schools, regions and the state should be informed by research evidence on practical models that are effective in meeting the cognitive and affective needs of children from ethnic minority backgrounds.